Construção de saberes e significações imaginárias na trajetória de vida de uma alfabetizadora cega - Oliveira, Biviane Moro de (2008)
This paper has been developed in the research line called Teachers Education, Knowledge and Professional Development, of the Post-Graduation Program in Education, at the Federal University of Santa Maria. It has attempted an approximation to imaginary significations and knowledge constructed throughout the life of a blind literacy class teacher. The main theoretical references have included the social imaginary, teacher s knowledge, the visual deficiency and the use of life histories as research sources. To carry out this study, the qualitative approach and the biographical method of life history have been employed to search for this teacher s history of knowledge construction and imaginary significations, through her autobiographical narratives and memories of her experiences as a blind literacy class teacher who has worked with the Braille system. From social imaginary theoretical contributions, it has been concluded that the subject of this research mobilizes her students, peers, school and the Association of Blind People to establish instituting significations, so as to show, from her life experience, some possibilities of instituted significations, which deny possibilities of professional exercise to the visual impaired and which, in a certain way, prevent both their social inclusion and total citizenship. In relation to the teacher s knowledge, it was verified that this knowledge is built through both personal and teaching experiences. Because of that, personal and experiential knowledge has prevailed. This research has also pointed out specific issues related to educational aspects of visual impairment, such as literacy through the Braille system, orientation and mobility, and use of specific resources. This study has enabled this life history, in its singularity, to contribute towards new proposals in terms of teachers education, teaching as a profession, and inclusion.